2016
DOI: 10.1017/s0022215116000931
|View full text |Cite
|
Sign up to set email alerts
|

Occult level IV metastases in clinically node-negative patients with oral tongue squamous cell carcinoma

Abstract: Supraomohyoid neck dissection appears to be an appropriate treatment for N0 tongue squamous cell carcinoma and there is no need for level IV lymph node dissection in a N0 patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Reports of level IV metastasis in N0 patients range between 1.5% and 6.3% and level IV skip metastasis to be 0%-3.1%. 8,[12][13][14] Motiee-Langroudis reported the highest rate of both level IV involvement (6.3%) and level IV skip metastasis (3.1%) for N0 patients. 12 The results likely reflect the small sample size of 32 where each patient represents a greater overall percentage.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Reports of level IV metastasis in N0 patients range between 1.5% and 6.3% and level IV skip metastasis to be 0%-3.1%. 8,[12][13][14] Motiee-Langroudis reported the highest rate of both level IV involvement (6.3%) and level IV skip metastasis (3.1%) for N0 patients. 12 The results likely reflect the small sample size of 32 where each patient represents a greater overall percentage.…”
Section: Discussionmentioning
confidence: 95%
“…8,[12][13][14] Motiee-Langroudis reported the highest rate of both level IV involvement (6.3%) and level IV skip metastasis (3.1%) for N0 patients. 12 The results likely reflect the small sample size of 32 where each patient represents a greater overall percentage. Despite the comparatively higher rates, the authors followed the Weiss criteria and recommended a level I-III neck dissection for N0 tongue SCC patients.…”
Section: Discussionmentioning
confidence: 95%
“…Other studies have also shown a higher rate of spread to level IV in oral tongue cancer and have also advocated removal of this level [182,183]. Conversely, some investigators have found a much lower rate of spread to level IV, anywhere from 0% to 6.25% and recommend only level I to III dissection in cases of early oral tongue SCC [184][185][186][187][188][189][190]. The surgical anatomical distinction of level III versus level IV is the position of the omohyoid muscle.…”
Section: Surgical Therapymentioning
confidence: 99%
“…For clinically and radiologically node-negative (cN0) patients with oral and oropharyngeal squamous cell carcinoma (OSCC and OPSCC), accurate detection of positive lymph nodes (LNs) in the neck is critical as there is a 25% chance of micrometastases with an associated 50% decrease in survival. 1,2 The sensitivity of available imaging modalities to detect cervical metastases is only 50%-70% 3 ; therefore, elective neck dissection (END) is performed for both staging and treatment. Sentinel lymph node biopsy (SLNB) avoids overtreatment of 75% of cN0 patients by providing equivalent diagnostic yield to END with less morbidity, 4,5 While SLNB is not broadly considered standard of care for head and neck cancers, the conventional method in which this procedure is performed typically relies on preoperative mapping of radionuclear tracers using scintillation detectors (e.g., lymphoscintigraphy following peritumoral injection of 99m Tc-nanocolloid), and intraoperative guidance to draining LNs via use of handheld gamma probes.…”
Section: Introductionmentioning
confidence: 99%